Development of Intellectual Testing for Electric Motor Installation in Vocational Education - Taruno, Djoko Laras Budiyo; Nugroho, Nur Rohman Eko (Universitas Dharma Wacana, 2023)
This study aims to understand the functionality of computerized adaptive testing software based on a website application model for the competency of electric motor installation in vocational education. The research method in this research uses research and development and the waterfall model. The research subjects are teachers and students in the electric motor installation subject. Data collection is done using the Noeeriat software instrument. The results of this study are as follows: (1) This tool can function well. This is indicated by testing on the authority of teachers (86.22%) and students (87.50%). (2) The usability level of the tool is considered very feasible in terms of functionality, display, and usefulness. (3) This tool contributes to an improvement in student learning outcomes. This tool can be used to measure the level of students' competency achievement, as a basis for compiling progress reports on learning outcomes, and as a foundation for improving the learning process.